A Longitudinal Study on the Perceived Roles of IT and the Corporate IT Function with Influences on CIOs’ Work Equilibria in a Media Company - Dahlberg Tomi; Hokkanen Päivi; Newman Mike (United States, 2022)
Our article investigates factors impacting IT executives’ equilibria of CIO work. We used the interview data collection method in a media company. Interviews revealed that the roles of IT and the corporate IT function were seen differently at three levels – social groups - of the company. During the years 2010-2016 our case company experienced several business interruptions. We investigated how two of them and the perceived roles of IT and the corporate IT function impacted three IT executives’ equilibria of CIO work by using the punctuated equilibrium model. Moreover, we used constructs from Granovetter’s social network theory to better understand why their perceptions and equilibria differed. The punctuated equilibrium model together with the constructs of the social network theory proved valuable in understanding the changes in the role perceptions and the equilibria of CIO work.
Proceedings of the 50th Hawaii International Conference on System Sciences